Obliterative bronchiolitis in fibreglass workers: a new occupational disease?. Issue 5 (15th January 2013) - Cullinan, Paul; McGavin, Clive R; Kreiss, Kathleen; Nicholson, Andrew G; Maher, Toby M; Howell, Tim; Banks, John; Newman Taylor, Anthony J; Chen, Chi-Hsien; Tsai, Perng-Jy; Shih, Tung-Sheng; Burge, P Sherwood
Abstract : Rationale and objectives: Obliterative bronchiolitis (OB) is a rare disease with a small number of established occupational aetiologies. We describe a case series of severe OB in workers making glass-reinforced plastics. Methods: Workplace exposures were the likely cause after the independent diagnosis of OB in two workers laying up the fibreglass hulls of yachts; the second worker took over the job of the first after he left following a lung transplant. Presentation of these two cases at international meetings led to others identifying similar workers. Main results: We identified six workers with good evidence of OB. All were involved in preparing fibreglass with styrene resins, five as boat builders laying up fibreglass hulls and one during cooling-tower fabrication. The disease came on rapidly without unusual acute exposures. Two patients had lung transplants, while another died while waiting for one. Histology confirmed OB in the four with biopsies/post-mortem examinations or explanted lungs. Conclusions: A rare, potentially fatal disease occurring in six workers laying up fibreglass with styrene resins from five different worksites suggests that work exposures were the cause of their OB. The precise agent responsible awaits identification.